Controlled empowerment of women: intersections of feminism, HCI and political communication in India. (April 2022) - Mangurkar, Isha; Rangaswamy, Nimmi
Twitter played a dominant role during the 2014 general elections in India, ushering a right-wing party into power. Political leaders employed Twitter to augment their public image and push right-wing campaign agendas to millions of followers. A prominent and strategic use of Twitter was credited to Prime Ministerial candidate Narendra Modi, portrayed as a visionary leader supporting economic development, social empowerment and good governance. Within this narrative, women's empowerment debates underwent multiple transformations. Through this article, we aim to establish the nature of discussions lying at the intersections of feminist thinking and internet technology. We study the discursive trajectory of women's empowerment against the backdrop of a right-wing political (Hindutva) ideology playing out on Twitter. Utilising the qualitative methods of Thematic Analysis and Feminist Relational Discourse Analysis, we study two cases highlighting feminist campaigns beginning in 2014: instant triple talaq, and the Sabarimala verdict. We analyse tweets in relation to these incidents and highlight the rhetorical inconsistency of right-wing leaders and supporters. We further discuss the implications of this inconsistency for the simultaneous suppression of voices demanding empowerment and amplification of those justifying religious tradition. Finally, we conclude by introducing the idea of the 'controlled empowerment' of women in support of our analysis.